KUALITAS BUTON EPURE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
,In connection to the needs of asphalt for pavement management, an effort to exploite deposit of Buton rock asphalt should be developed Buton asphalt with low content of bitumen under heterogen condition should be improved. The effort of exploiting Buton rock asphalt is covered an improvement of condition, quality of bitumen, and quality of filler, so competitive asphalt and filler to other materials would be found. Solvent extraction is carried out to draw the bitumen from Buton rock asphalt mineral. Treated extract bitumen and selected extract filler are mixed under a certain composition, than this mixture is called Buton Epure. Buton Epure is a kind of new binder, the quality can be tested by references with can be created from a mixture of petroleum asphalt and extract filler of Buton rock asphalt under same composition. From this research indicate that Buton Epure 55 of petrolene (BE55p) with additive of minarex 5% has quality closed to the Esso Buton Epure 55. For Asphalt Mixing Plant, as a binder this BE55p has fullfilled the viscosity specification of 200 - 400 cst under 94 - 100Â° C.